SISTEM PENDUKUNG KEPUTUSAN PENENTUAN TINGKAT RADIKALISME MENGGUNAKAN METODE FUZZY INFERENCE SYSTEM - Afisima Dewima; Celvin Gazinda; Fawwaz Afif Alvia; Irene Faizah Miranda; Moh Khusnul Mubarak; Moch. Affan Nurudin; Syarifah Norahanum Hanifah; Muhammad Nabil Alfi (e-NARODROID, 2019)
Radicalism has developed so rapidly. This has become homework for all of us so that radical ideologies do not become more widespread. So it is necessary to make an approach to make decisions regarding the level of understanding of radicalism whether or not it has that understanding. There are 4 things related to radicalism ideology, namely 1. Tolerance, 2. Social, Economy, and Politics, 3. Understanding of Culture 4. Religious Values. 4 The cases mentioned are used as Parameters. Within these parameters, each has a sub parameter, in the Tolerance parameter has 4 sub parameters, Social, Economic, Political parameters have 4 sub parameters, Culture parameters have 3 sub parameters, Religious parameters have 4 sub parameters. The method used in this study is a Fuzzy Inference System. Fuzzy Inference System has 4 processes including fuzzification, inference system, defuzzification, and rule base. The results of this study are a decision, in which there are 3 decision criteria, namely Moderate, Conservative and Radical. Keywords:Radicalism, Parameters, Fuzzy Inference System